Assessing the severity of acute pulmonary embolism: A review of epidemiological, clinical, biological, and CT angiography parameters - Jean-Pierre Tshungu Muteleshi; Tacite Mazoba Kpanya; Jean Tshibola Mukaya (Orapuh Journal)
Pulmonary embolism (PE) presents with diverse clinical manifestations, which often do not correlate with the size of the clot. Common symptoms such as dyspnea and pleuritic chest pain are frequent but nonspecific, complicating clinical diagnosis. This review aims to assess the severity of acute pulmonary embolism by examining epidemiological, clinical, biological, and computed tomography (CT) angiography parameters to improve diagnostic accuracy and prognostic evaluation. Clinical diagnostic scores and electrocardiogram (ECG) findings are supplemented by D-Dimer assays in cases with low or intermediate clinical probability. Chest X-rays are recommended urgently at the bedside to exclude alternative causes of dyspnea and to assess suitability for ventilation/perfusion scans. Transthoracic cardiac Doppler ultrasound evaluates hemodynamic impact. Definitive diagnosis is established by chest CT angiography, which has largely replaced traditional angiography and lung scintigraphy. D-Dimer testing demonstrates a high negative predictive value (~95%) when clinical probability is low or intermediate, effectively ruling out venous thromboembolism (VTE) when negative. Chest X-rays may appear normal within 24 hours or show signs such as moderate pleural effusion, band atelectasis, or pulmonary infarction evidenced by Hampton’s hump. Cardiac Doppler ultrasound reveals signs indicative of PE including right ventricular dilation (>25 mm), interventricular septum displacement, and pulmonary artery trunk enlargement. CT angiography identifies acute PE by detecting central intravascular hypodensities with iodinated contrast, often forming acute angles with vessel walls. The integration of clinical, biological, and imaging parameters, particularly CT angiography, enhances the accuracy of acute PE diagnosis and assessment of severity. Prompt bedside imaging and ultrasound provide critical information to differentiate PE from other severe conditions. CT angiography remains the gold standard for confirming clinical suspicion and guiding urgent management.